2018
DOI: 10.1039/c7qm00588a
|View full text |Cite|
|
Sign up to set email alerts
|

High-efficiency ultrapure green organic light-emitting diodes

Abstract: Efficient ultrapure green OLEDs were demonstrated by using a platinum complex (PtN7N) and a top emitting structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…Similar phenomenon was also observed in the previous report of narrowband green emitter PtN1N vs. PtOO3 [62]. Moreover, Fukagawa's work also demonstrated that the operational stability of PtN7N-based OLEDs could be comparable to that of the Ir(mppy) 3 -based ones, indicating the promise for the practical application of PtN7N by employing suitable host and charge-transporting materials [60,63].…”
Section: Other Types Of Tetradentate Platinum(ii) Complexessupporting
confidence: 85%
See 3 more Smart Citations
“…Similar phenomenon was also observed in the previous report of narrowband green emitter PtN1N vs. PtOO3 [62]. Moreover, Fukagawa's work also demonstrated that the operational stability of PtN7N-based OLEDs could be comparable to that of the Ir(mppy) 3 -based ones, indicating the promise for the practical application of PtN7N by employing suitable host and charge-transporting materials [60,63].…”
Section: Other Types Of Tetradentate Platinum(ii) Complexessupporting
confidence: 85%
“…Very recently, Fukagawa and co-workers reported great progress in ultrapure green OLEDs based on a NHC emitter PtN7N [60], which was developed by Li′s group before 2014 [61]. The optimized OLED showed CIE coordinates of (0.18, 0.74) using a top-emitting OLED with a microcavity structure and also using a boron-based host material [60].…”
Section: Other Types Of Tetradentate Platinum(ii) Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] The broad emission band creates a restriction for TADF materials to satisfy the requirement of high color purity displays based on R/G/B (red/green/blue) emitters. [ 7 ] Although the color purity of original broad electroluminescence (EL) band can be modified by introducing a color filter and/or an optical microcavity in commercial OLED displays, the modification leads to significant increase in cost and power consumption. [ 8–10 ] Thus, the development of efficient narrowband emissive materials, especially those able to achieve high color purity that comply with the Commission Internationale de L'Eclairage (CIE) coordinates requirements defined by the broadcasting standards, is highly important.…”
Section: Figurementioning
confidence: 99%